NFC TECHNOLOGY AND ITS DEVELOPMENT PROSPECTS - SHAPOVALOVA, Kateryna; SHEREMETA, Polina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines a system for making contactless payments using NFC technology. The practice of acquiring as a trade method that increases the attractiveness of business for the client and simplifies trade processes for owners and employees is considered. The relevance of such a system in Ukraine and the prospects for its development have been determined. The presence on the market of such systems, combinations of systems that allow to obtain the same attractiveness for business and customers was analyzed. Despite the fact that such systems attract customers to the business, the number of services that can provide relevant services to the customer or business remains insignificant, and ready-made solutions combining functionality for the customer and the seller at the same time have not been found to date. The purpose of the article is to present the stages of development of contactless payment systems that transfer data between client applications using NFC technology and a server based on microservice architecture. The article presents a system of contactless payments based on NFC technology, its structure and algorithm of operation. It is indicated that the principle of operation consists in receiving and transmitting data from two end customers of the system to one of the payment systems in a certain order, which allows for safe payment transactions.